Positional interchanges influence the physical and technical match performance variables of elite soccer players - Schuth, G.; Carr, G.; Barnes, C.; Carling, C.; Bradley, P. S. (Journal of Sports Sciences, 2016)
Positional variation in match performance is well established in elite soccer but no information exists on players switching positions. This study investigated the influence of elite players interchanging from one position to another on physical and technical match performance. Data were collected from multiple English Premier League (EPL) seasons using a computerised tracking system. After adhering to stringent inclusion criteria, players were examined across several interchanges: central-defender to fullback (CD-FB, n = 11, 312 observations), central-midfielder to wide-midfielder (CM-WM, n = 7, 171 observations), wide-midfielder to central-midfielder (WM-CM, n = 7, 197 observations) and attacker to wide-midfielder (AT-WM, n = 4, 81 observations). Players interchanging from CD-FB covered markedly more high-intensity running and sprinting distance (effect size [ES]: -1.56 and -1.26), lost more possessions but made more final third entries (ES: -1.23 and -1.55). Interchanging from CM-WM and WM-CM resulted in trivial to moderate differences in both physical (ES: -0.14-0.59 and -0.21-0.39) and technical performances (ES: -0.48-0.64 and -0.36-0.54). Players interchanging from AT-WM demonstrated a moderate difference in high-intensity running without possession (ES: -0.98) and moderate-to-large differences in the number of clearances, tackles and possessions won (ES: -0.77, -1.16 and -1.41). The data demonstrate that the physical and technical demands vary greatly from one interchange to another but utility players seem able to adapt to these positional switches.